Establishing the content validity index of Post Occupancy Evaluation (POE) of green building in Malaysia / Mohamad Tajudin Saidin ... [et al.] - Saidin, Mohamad Tajudin; Mohammad, Izran Sarrazin; Yop Zain, Fairiz Miza; Lop, Nor Suzila (Universiti Teknologi MARA, Perak, 2020)
A green building focuses on increasing the efficiency of resources in term of energy, water and materials, while at the same time reducing the building impact on human health and the environment during the building's lifecycle. Green buildings are significant in operational savings and are able to increase workplace productivity. There are 909 registered green buildings project up to September 2019 in Malaysia. However, previous research indicated the success of green building in term of its performance is still in doubt and very much speculative. In fact, there have also been reports saying that green building fails to perform appropriately. Unfortunately, up until now there are no standard performance criteria and performance parameters to measure the green building performance in Malaysia. Thus, the aim of this paper is to present the findings of the research which identify the performance criteria and parameters of Post Occupancy Evaluation (POE) for green building in Malaysia. Fifteen (15) performance criteria and thirty-five (35) parameters were identified from the literature and validated by green building experts by using Content Validity Index. The finding identifies eleven (11) performance criteria and twenty-six (26) performance criteria to measure the green building performance through POE. The findings from this research may turn as a new knowledge which identifies the performance criteria and performance parameters to conduct 76 Malaysian Journal of Sustainable Environment Post Occupancy Evaluation (POE) for green building in Malaysia. Thus, government or private developer can use these performance criteria and performance parameters to measure their green building performance. This research was conducted within the context of Malaysian construction industry, thus, it cannot be generalised to other countries.